Silicone-induced granuloma, hypercalcemia and chronic kidney disease in a transgender patient - Cardoso Barros, Tattieri Alenninne; Narciso Júnior, José; Cunha Lima Alcântara, Aline; da Silva Junior, Geraldo Bezerra; Lima, Rafael Siqueira Athayde (Journal of Health & Biological Sciences, 2024)
Background: hypercalcemia mediated by a silicone-induced granulomatous reaction is a condition that, despite being rare, must be remembered since there is an increasing demand for aesthetic procedures among the general population. It is necessary to rule out other causes of hypercalcemia, such as hyperparathyroidism, hypercalcemia of malignancy, infectious and non-infectious granulomatous diseases, as well as the use of drugs. Case presentation: We present a patient with a history of large amounts of silicone implants who was admitted to a hospital presenting hypercalcemia and chronic kidney disease. A skin biopsy revealed a granulomatous foreign body reaction associated with exogenous siliconomatous material. Treatment with corticosteroids was initiated, with partial renal function improvement, with no renal replacement therapy needed. Conclusion: Patients with silicone implants should be carefully monitored for renal function and may be informed to avoid nephrotoxic agents as there is sufficient evidence that this type of aesthetic procedure can trigger hypercalcemia and CKD.